Therapeutic Communication for Rehabilitation Counselors Social Narcotics, Psychotropics and Active Substances (Napza) Foundation Sekar Mawar Bandung in Increasing Resident’s Self-Confidence - Surya, Desayu Eka; Santika, Fahira (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Therapeutic communication is a communication context that is no less important than other communications. Therapeutic communication is interpersonal communication between nurses and patients, in which the nurse will gain shared learning experiences in improving the patient’s emotional experience. The research objective is to explain and tell about the phases of therapeutic communication carried out by the Sekar Mawar Bandung Foundation for Drug Rehabilitation which includes Pre-interaction, Orientation Phase, Work Phase and Termination Phase. By using a qualitative approach with descriptive methods, through non-participant observation data collection techniques, in-depth interviews, literature study and documentation, determination of research informants using snowball sampling and data analysis techniques data reduction, data collection, data presentation and drawing conclusions, the results obtained shows that in doing therapeutic communication communication planning is needed, starting from the introduction between the nurse and the patient, before the nurse takes recovery actions and makes the patient confident to join and reunite with their social environment. This study concludes that the therapeutic communication carried out by the nurse to the patient can restore the patient’s confidence. This study can provide information for the patient’s family who needs information about the strength of the nurse’s therapeutic communication to the patient.